PENGARUH NET PROFIT MARGIN DAN EARNING PERSHARE TERHADAP HARGA SAHAM SYARIAH DI PT. INDOFOOD CBP SUKSES MAKMUR TANJUNG MORAWA TAHUN 2015-2019 - Raudhatul Hasanah (MUTLAQAH: Jurnal Kajian Ekonomi Syariah, 2021)
As we know that share ownership is proof that the person concerned is part of the owner of the company. The bigger the shares he owns, the greater his power in the company. There is also a major factor that causes stock prices to change, namely the different perceptions of each investor according to the information they have. These different perceptions occur due to different analyzes used by investors.The cause of changing stock prices is that which affects stock prices, one of which is the announcement of the company's financial statements including Net Profit Margin and Earning Pershare and others. This study aims to determine how the effect of Net Profit Margin and Earning Pershare on Sharia Stock Prices at PT. Indofood CBP Sukses Makmur 2015-2019. The research method used is the classical assumption test, multiple linear regression test, and hypothesis testing. The sample in this study is the Company Financial Statements of PT. Indofood CBP Sukses Makmur 2015-2019. The data used in this research is secondary data.The results showed that partially Net Profit Margin had an effect of 1.697 with a significant level of 0.049 on Sharia Stock Prices. And Earning Pershare has no influence with a value of 0.606 with a significant level obtained of 0.547 on Sharia Share Prices. Simultaneously, Net Profit Margin and Earning Pershare affect the Sharia Stock Price of 31,222 with a significant level of 0,000.Meanwhile, the result of the determinant coefficient (R2) shows that the effect of Net Profit Margin and Earning Pershare has an effect of 0.016% on disclosure. This shows that 16% of disclosure is influenced by Net Profit Margin and Earning Pershare. While the remaining 84% is influenced by other variables not examined in this study.